Modelling of Diagnostics Influence on Control System Safety - Rástočný, Karol; Ždánsky, Juraj; Franeková, Mária; Zolotová, Iveta (COMPUTING AND INFORMATICS, 2018)
If the control system besides the standard control functions also realizes the functions (known as safety functions), failures of which can influence safety of the controlled process, then the control system may be a source of risk for assets, that are within the scope of the controlled process. Early detection of these failures and subsequent negation of their effects can have a significant influence on the safety integrity level of the safety function and thus also on the elimination of risks related to the controlled process. Therefore, the diagnostics is the means which, if appropriately applied, can increase not only the availability, but also the safety of the control system. The paper deals with using the homogeneous Markov chains to influence the evaluation of on-line diagnostics on the hardware safety integrity of the safety function, depending on the application method of several simultaneously operating diagnostics mechanisms and their basic parameters - the failures diagnostic coverage coefficient and the failure diagnostics time.